Esthetics and Methods in the Study of Sexual Rights. (December 2017) - Goldberg-Hiller, Jonathan
The study of sexuality has been and remains a seminal project for Social & Legal Studies. This article utilizes the political/esthetic theory of Jacques Rancière in order to explore the dimensions of this project as an intervention in the field of sociolegal studies from the Journal's inception to contemporary concerns. Early studies of sexuality in the Journal developed three methodological themes: law as deconstructable process, as consequential for the performative aspects of nonessentialized identities, and as potentially destabilized by highly mobile rights claiming. This article seeks to understand whether this unique agenda for the study of gender, sexuality, and law remains viable. It concludes that the nonessentialist fluidity of gender and sexuality which framed early approaches to the study of the consequences of rights and the relationship of sexual and gender identity requires renewed attention to the structures of race, colonialism, and imperialism enabling and enabled by contemporary queer critique.